Impacts of climate change scenarios on European ash tree (Fraxinus excelsior L.) in Turkey - Varol, Tuğrul; Canturk, Ugur; Cetin, Mehmet; Özel, Halil Barış; Sevik, Hakan (Elsevier BV, 2021)
Abstract Climate change is expected to have various impacts on forest ecosystems through drought, heat stress, insect invasions and forest fires. Therefore, lack of taking the necessary measures in time will lead to the extinction or endangerment of valuable species. The entropy method was used in order to estimate the geographic distribution of Fraxinus excelsior L. available in Turkey under present and future climate conditions. 19 bioclimatic variables obtained from the monthly data within 30 provinces, where Fraxinus excelsior L. was found in Turkey, as well as the topographic variable of elevation were used in the modelling process. The results show that Fraxinus excelsior L. is largely affected by precipitation in the driest month, the driest quarter and the hottest quarter. According to the response curve of Fraxinus excelsior L. in Turkey, it is observed that it prefers the habitats with average precipitation of 22 mm in the driest month, average precipitation of 100 mm in the driest quarter and the precipitation over 70 mm in the hottest quarter. The SSPs 245 and SSPs 585 climate scenarios, respectively, show that the geographic distribution of Fraxinus excelsior L. will narrow by 7.58% and 6.28% in 2100. All of these results show that species response to the individual and communal impacts as well as the impacts at ecosystem scale dictated by climate change by changing their climatic niches. Most of the plant species that lack an effective and rapid migration ability will have difficulty in finding suitable habitat areas. Thus, the ecological consequences of the narrowing experienced in the foreseen borders may have serious consequences for both the management and protection of forests.
Keywords: Turkey; Evolution; Climate change scenario; Response; Indexes; Disturbance; Management, Monitoring, Policy and Law; Fraxinus Excelsior L; Fraxinus excelsior L; Species Distributions; Maximum entropy; Local Adaptation; Phenotypic Plasticity; Responses; Nigra; Climate Change Scenario; Forest; Maxent; Maximum Entropy; Future; 15. Life on land; 13. Climate action